2022
DOI: 10.3390/medicina58020214
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis for Potential Kidney Transplant Recipients: Pride or Prejudice?

Abstract: Kidney transplantation (KT) is recognized as the gold-standard of treatment for patients with end-stage renal disease. Additionally, it has been demonstrated that receiving a pre-emptive KT ensures the best recipient and graft survivals. However, due to an overwhelming discrepancy between the organs available and the patients on the transplant waiting list, the vast majority of transplant candidates require prolonged periods of dialysis before being transplanted. For many years, peritoneal dialysis (PD) and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 206 publications
(241 reference statements)
0
14
0
Order By: Relevance
“…18,19 However, due to the rapid increase in ESRD incidence and the chances of transplantation is low, the vast majority of these patients living with PD or HD throughout their lives. [20][21][22] Studies comparing the patient groups on psychiatric morbidity, which is frequently seen in CKD, can provide a valuable idea about which dialysis method can be preferred at first. Depression is a common psychiatric disorder in dialysis patients.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…18,19 However, due to the rapid increase in ESRD incidence and the chances of transplantation is low, the vast majority of these patients living with PD or HD throughout their lives. [20][21][22] Studies comparing the patient groups on psychiatric morbidity, which is frequently seen in CKD, can provide a valuable idea about which dialysis method can be preferred at first. Depression is a common psychiatric disorder in dialysis patients.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…The advantage of PD over ICHD is that PD can be performed at home by patients, without the need to travel to a hemodialysis center, with increased flexibility and freedom. Accumulating evidence demonstrated that PD has been a cost-saving treatment compared to ICHD in most developed countries and some developing countries [ 4 , 6 ]. The current policy in Taiwan tends to be “PD-Favored”, which means the government’s dialysis policy encourages the use of PD as the treatment option while removing any existing disincentives [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study has found that HCPs may offer PD as an option more often to patients with higher health literacy or better self-care abilities [ 7 ]. Although PD emphasizes flexibility and freedom as its advantages, renal replacement therapy must be tailored to the specific needs and preferences of the patient [ 6 , 16 ]; thus, PD is not always the most appropriate treatment modality for the patient. Inadequate patient education might result from the candidacy bias of physicians and nurses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consolidated knowledge and evidence-based care constantly mutate to adapt new scientific advances to old and emerging clinical or surgical challenges. Necessarily, the progressive changes in our praxis contribute to addressing the issues we face every day, from the well-established [ 1 , 2 , 3 ] to the uncommon ones [ 4 ], as well as to the unprecedented crisis caused by the ongoing SARS-CoV-2 pandemic [ 5 ].…”
mentioning
confidence: 99%
“…Once recognized as poor transplant candidates, this complex group of recipients is now routinely transplanted with encouraging long-term recipient and allograft survivals [ 4 ]. In a provocative manuscript, Nardelli and coworkers questioned the preferential use of hemodialysis over peritoneal dialysis in patients awaiting a KT, promoting a more flexible (and perhaps less biased) vision of the two renal replacement modalities [ 3 ]. Lastly, the systematic review performed by the group of researchers from Tor Vergata University summarized current trends in the management of immunosuppression in KT recipients with SARS-CoV-2 infection [ 5 ].…”
mentioning
confidence: 99%